Use of training denture base and palateless dentures: Two different strategies in the management of severe gag reflex in edentulous patients - Medha Vivek Bhuskute (Wolters Kluwer Medknow Publications, 2020)
Gagging is a common problem encountered in clinical prosthodontic practice. In many cases gagging is of psychologic nature and should be treated before denture procedures are completed, so that the patient will be comfortable with well-constructed prostheses. Effective management of gag reflex includes a wide array of techniques ranging from use of common salt on the tip of tongue, acupressure, distraction, relaxation, pharmacotherapy and desensitization. This case report discusses how a holistic approach for gagging prevention and use of training denture base can facilitate denture wearing for a known potential gagger and also highlights how palateless denture helped overcome gagging in a patient with thick ropy saliva in another case.